A novel Gaussian higher-order plate theory for dynamic response of porous sandwich plates with different geometries. (April 2023) - Yushan, Xiao; Zhen, Wu; Xitao, Zheng; Leilei, Yan; Xiaohui, Ren
Abstract: With the wide application of lightweight structures, it is necessary to precisely and efficiently predict dynamic response of sandwich plates for the dynamic safety of sandwich structures in service life. Due to the weak normal stiffness of the core, the used higher-order shear deformation theories (HSDTs) are required to consider the transverse normal strain. To the best knowledge of authors, the most efficient and accurate higher-order theory including transverse normal strain merely contains six independent unknowns. However, the existing six-unknown higher-order theories may be incapable of accurately forecasting the dynamic response of the soft-core sandwich plates attributing to the huge mismatches of mechanical properties. Therefore, a novel Gaussian higher-order plate theory (NGHPT) with six independent variables has been developed for the free and forced vibration of sandwich plates, where the transverse shear function is defined by Gaussian function and Fourier transformation to approximately fulfill the continuity requirement of transverse shear stresses at the interfaces. Meanwhile, the isogeometric analysis (IGA) is utilized to handle complex geometries. Compared to the existing HSDTs with six unknowns, the NGHPT can more accurately predict the dynamic behaviors of sandwich plates, which is verified by several experimental tests. Furthermore, a comprehensive parametric study on various sandwich plates including square, circular, elliptical and annular shapes, has been carried out to evaluate the influence of fiber orientation, distribution of internal pores and porosity coefficient on the dynamic response, which can provide suggestions for the future designs of porous sandwich plates to meet specific dynamic requirements. Highlights: A novel Gaussian higher-order plate theory is developed by Gaussian function and Fourier transformation. Several vibration tests on the CFRP sandwich plates with various fiber orientations are carried out. Effects of fiber orientation and porosity coefficient on free and forced vibration are investigated.